EVALUASI KEBERHASILAN IMPLEMENTASI SIMRS DI RUMAH SAKIT X KABUPATEN JEMBER DENGAN PENDEKATAN METODE TTF - Suhartatik Suhartatik; Doni Setiawan Hendyca Putra; Sustin Farlinda; Andri Permana Wicaksono (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
X Hospital in Jember regency applies a hospital management system or hospital information system (SIMRS) since 2012. The results of a pilot study conducted by the researcher showed that there are still several issues in the implementation of hospital management information systems (SIMRS) including data mismatches and incomplete features. The objective of this study was to evaluate the success of the SIMRS implementation at X Hospital in Jember regency using the Task Technology Fit (TTF) theory. This study was quantitative research. Data collection techniques used questionnaires with a total of 54 respondents as the sample. The results showed that the identification of the TTF variable at the X Hospital in Jember regency showed that the Task Characteristic (TAC) had a total score of 80.1%, Technology Characteristic (TEC) had a total score of 77.5%, Task Technology Fit (TTF) had a total score. 78.17%, Performance Impact (PI) has a total score of 78.19%, and Utilization (U) has a total score of 80.25%. The suggestion proposed by the researcher regarding the above problems is that the hospital needs to make improvements and development of systems related to data consistency, feature completeness, and feature optimization in SIMRS according to user needs to increase the success of its implementation.